Developing New Allometric Models for Estimating Aboveground Woody Biomass and Volume of Populus euphratica Using Terrestrial Laser Scanning - Asadilla Yusup; Xiaomei Hu; Ümüt Halik; Tayierjiang Aishan; Maierdang Keyimu; Hao Bai; Shengli Tao (Journal of Remote Sensing)
Populus euphratica is an endangered species in desert riparian forests along the Tarim River in the arid region of northwestern China. Accurately estimating aboveground biomass is essential for assessing the growth status of P. euphratica, but is challenging as harvesting P. euphratica is strictly prohibited. In this study, we developed new allometric equations to estimate the woody aboveground biomass and volume of P. euphratica based on data collected along 200 km of the lower Tarim River. Our approach is nondestructive as it combines terrestrial laser scanning and quantitative structure modeling. We found that quantitative structure model effectively acquired tree 3D structures from high-density point clouds. The total volumes of the sample trees were found to range from 0.01 to 4.25 m3, and aboveground biomass from 3.07 to 1,997.41 kg, with 86% of the trees having a biomass below 500 kg. The biomass of large trees has been underestimated by previous allometric equations due to the limited sample sizes used to build the models. Our new allometric equations utilizing diameter at breast height and tree height ([Formula: see text]; [Formula: see text]) showed less bias (R2 ≥ 0.94) since our data encompass not only small-sized but also large trees, resulting in a reduction of RMSE by 40% to 50% compared to previous models. When tree height was not available, diameter alone also provided high accuracy for estimating biomass ([Formula: see text]) and volume ([Formula: see text]), with R2 values of 0.93. Our research provides a nondestructive method to accurately estimate the biomass of P. euphratica, contributing to improved forest conservation and carbon storage assessment in the desert riparian forest.